Arecoline inhibits endothelial cell growth and migration and the attachment to mononuclear cells - Shuei-Kuen Tseng; Mei-Chi Chang; Ming-Lun Hsu; Cheng-Yao Su; Lin-Yang Chi; Wen-Chien Lan; Jiiang-Huei Jeng (Elsevier, 2014)
Background/purpose: Betel quid (BQ) chewing is a popular habit in South-Asian and Southeast Asian countries, and Taiwan. BQ chewing can cause oral cancer and oral submucous fibrosis, and increases the risk of cardiovascular diseases. However, how BQ chewing affects endothelial cells and is involved in cardiovascular diseases and vascular changes is not fully understood. The effects of arecoline, a component of BQ, on the growth and migration of endothelial cells (EAhy 926), and their adherence by U937 cells were investigated. Materials and methods: EAhy926 endothelial cells were cultured and exposed to various concentrations of arecoline for 24 hours. Morphological changes were observed using phase-contrast microscopy. Cytotoxic effects were analyzed using a 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay. A wound closure assay was used to evaluate the cellular migration of EAhy926 cells. The attachment of 2',7'-bis-(2-carboxyethyl)-5-(6)-carboxyfluorescein-labeled U937 cells to EAhy926 endothelial cells that were pretreated with various concentrations of arecoline was further studied. Results: The addition of arecoline at concentrations >0.4 mM significantly decreased cellular viability. EAhy endothelial cells showed marked morphological changes, and cellular migration decreased after 24 hours and 48 hours of exposure to arecoline. The number of U937 cells attached to EAhy 926 cells increased when endothelial cells were pretreated by arecoline. Conclusion: Arecoline impaired vascular endothelial cells by inhibiting their growth and migration and their adhesion to U937 mononuclear cells. These results reveal that arecoline may contribute to the pathogenesis of oral submucous fibrosis and cardiovascular diseases by affecting endothelial cell function in BQ chewers.